A Comparative Analysis Of Financial Performance Of Conventional And Islamic Banks In Indonesia - et. al., Suskim Riantani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to analyze the differences in financial performance between conventional banks and Islamic banks. Financial performance is measured through capital, asset quality, earnings, and liquidity. The unit of analysis was carried out on conventional banks and Islamic banks during the research period of 2014-2018. This research uses descriptive and comparative methods. The sampling method used was two-stage cluster sampling and purposive sampling. Observations were made on three conventional banks and three Islamic banks. The method of analysis used a mean difference test with the t test statistic at a significance level of 5%. The results showed that there was a significant difference in the capital of conventional banks and Islamic banks, conventional banks had better capital performance than Islamic banks. There is a significant difference between the asset quality of conventional banks and Islamic banks. Conventional banks have better asset quality performance than Islamic banks. There is a significant difference in earnings between conventional banks and Islamic banks. Conventional banks have better earnings performance than Islamic banks. There is a significant difference between the liquidity of conventional banks and Islamic banks. Islamic banks have better liquidity performance than conventional banks.